Experimental Studies on Durability Studies of Concrete with Partial Replacement of Cement by Water Hyacinth Ash - Murugesh, V.; N. Balasundaram, Dr.; T. Senthil Vadivel, Dr. (International Journal of Engineering and Technology, 2018)
Cement is the main constituent ingredient in concrete. Now days many investigations undergone for substitute of cement due to green houses effect and global warming  .Many new products like rice husk ash, egg shell powder, baggage ash, etc are used as an effluent replacement material for cement. The new and Practical material for substitute of cement is water hyacinth ash .Water hyacinth ash (WHA), is used as an effectual replacement of partial cement, and it has been proved in several characteristics of concrete. The main important parameters in concrete are strength, durability and workability. In this paper, 10 % of cement replaced by water hyacinth ash   to investigate the effects of WHA on  durability and Strength  in concretes. On this basis, specimens were engrossed in water and acid to study the absorption property, acid attack and compared to conventional concrete. The test results show that replacement of cement by WHA in concrete has improved the parameters of concrete.